Propofol, An Alternative to Amobarbital in Wadas Test in Electro corticography Based Epilepsy Surgery for Determining Dominance of Brain - Rajbhandari, Pravesh; Shrestha, Pranaya; Acharya, Samir; Shretha, Resha; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Amobarbital which is used rampantly for Wadas test is not available in Nepal and to find a dominant hemisphere in a functional Electro corticography (ECoG) based epilepsy surgery is a must. So we have used propfol under Digital Subtraction Angiography (DSA) for both cerebral hemisphere. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 116-118